Formulation of Secondary Meaning Evidence in Trademark Infringement Disputes in Indonesia (Comparative Study of the United States and Thailand) - Safitri, Nadila; Suherman (Universitas Medan Area, 2024)
This study aims to analyze the regulation of secondary meaning and the formulation of proving secondary meaning within the trademark legal regime in Indonesia. The research employs a normative juridical method, supported by statutes, conceptual, and comparative approaches. The data used in this study consist of legal instruments such as Law Number 20 of 2016 concerning Trademarks and Geographical Indications, the TRIPs Agreement, the US Lanham Act, and Trademark Law. The results of this study indicate that Indonesia has not yet accommodated the regulation of secondary meaning in Law Number 20 of 2016 concerning Trademarks and Geographical Indications. In practice, there is no clear standard to determine whether a descriptive mark has acquired secondary meaning, which leads to case-by-case proof. It contrasts countries such as the United States and Thailand, which are provisions for proving secondary meaning. The absence of a provision for proving secondary meaning creates a legal vacuum when trademark infringement disputes arise. Therefore, there is a need for legal reform to regulate the proof of secondary meaning in trademark cases. A formulation for proving secondary meaning could be incorporated into Article 76 of Law 20/2016, which addresses trademark cancellation, by providing an exception for trademarks that have established secondary meaning through consumer association. Alternatively, the proof of secondary meaning could be considered during the substantive examination of trademark registration.